Perception of Plagiarism among Students of Higher Education in Indonesia - Fatimah Fatimah; Istiqomah Wulandari (Universitas Brawijaya, 2018)
Many definitions of plagiarism fall under the core concept of any activity in using, imitating or owning partially or completely of ideas, thoughts, works, and organizations from others without appropriate cita-tion and acknowledgement. Since this academic dishonesty has negative impacts, it needs to be overcome. The present researchers believe that student in Study Program of English, Brawijaya University are at risk of committing plagiarism. Therefore, this present research attempts to investigate the students’ perception of plagiarism in Study Program of English. The students’ perception investigated in this research deals with the students’ understanding on what actions that they categorize as plagiarism. This research employs descriptive quantitative approach since the data are obtained from the questionnaire, which is adapted from a questionnaire proposed by Marshall and Gary (2005).The participants of this study are 154 sixth semester students in Research Proposal Writing course. The results prove that they have basic concept of plagiarism and know how to put them accordingly to the academic regulation of how to cite other works in order not to commit plagiarism. However, the idea of self-plagiarism is not fully understood by the students.